Prehypertension in early versus late pregnancy. (17th January 2019) - Rosner, Jonathan Y.; Gutierrez, Megan; Dziadosz, Margaret; Bennett, Terri-Ann; Dolin, Cara; Pham, Amelie; Herbst, Allyson; Lee, Sarah; Roman, Ashley S.
Abstract: Introduction: Hypertensive disorders play a significant role in maternal morbidity and mortality. Limited data on prehypertension (preHTN) in pregnancy exist. We examine the risk of adverse outcomes in patients with preHTN in early (<20 weeks) versus late pregnancy (>20 weeks). Materials and methods: Retrospective cohort study of singleton gestations between August 2013 and June 2014. Patients were divided based on when they had the highest blood pressure in pregnancy, as defined per the Joint National Committee 7 (JNC-7). Groups were compared using χ 2, Fisher's exact, Student's t -test, and Mann–Whitney U test with p < .05 used as significance. Results: There were 125 control, 95 early preHTN, 136 late preHTN, and 21 chronic hypertension (CHTN). Early preHTN had an increased risk of pregnancy-related hypertension (PRH) (OR 12.26, p < .01) and composite adverse outcomes (OR 2.32, p < .01). Late preHTN had an increased risk for PRH (OR 4.39, p = .02) compared with normotensive and decreased risk for PRH (OR 0.26, p = .02), and composite adverse outcomes (OR 0.379, p = .04) compared with CHTN. Compared with late preHTN, early preHTN had more PRH (OR 2.85, p < .01), and composite adverse outcomes (OR 1.68, p = .04). Conclusions: Early prehypertension increases the risk of adverse obstetrical outcomes. Other than an increased risk of PRH, patients with late prehypertension have outcomes similar to normotensive women.